The effect of Fe2O3 catalyst on direct carbon fuel cell performance. (15th October 2015) - Skrzypkiewicz, Marek; Lubarska-Radziejewska, Iwona; Jewulski, Janusz
Abstract: In a direct carbon solid oxide fuel cell (DC-SOFC), solid carbonaceous fuel is supplied directly to SOFC anode. This approach offers advantages of high efficiency, system simplicity and possibility of direct conversion for a wide range of solid, carbonaceous fuels. Additional improvements in the cell performance can be achieved with the application of catalysts. Two alternative approaches have been considered to apply catalysts in a DC-SOFC configuration. In the first approach, activated carbon has been impregnated with inexpensive Fe2 O3 catalyst before supplying to the anode compartment as a fuel. In the alternative approach, SOFC anode has been impregnated with Fe2 O3 catalyst while the non-catalyzed activated carbon was supplied to the anode as a fuel. In both cases, the current density for a fuel cell operating at 0.7 V, more than doubled in comparison to previously reported results in a similar test setup. This result points to the reverse Boudouard reaction (C + CO2  → 2CO) as a limiting process for the fuel cell performance. Utilization of the in-situ generated CO improved for catalyst-impregnated anode, enabling higher conversion efficiency. Moreover, the impregnation of anode with Fe2 O3 consumes 17-times less catalyst than impregnation of carbon, with similar cell performance. The obtained results were compared to other DC-SOFC performance improvement approaches reported in the literature. Highlights: Application of Fe2 O3 catalyst yields improved DC-SOFC performance of 130–150 mW/cm 2 . Two approaches tested: Fe2 O3 impregnated anode and Fe2 O3 impregnated fuel. Impregnation of anode with Fe2 O3 consumes 17-times less catalyst than impregnation of carbon. The Fe2 O3 impregnated anode performance is close to that of anode operated on impregnated fuel.